2014
DOI: 10.1111/etap.12125
|View full text |Cite
|
Sign up to set email alerts
|

Are Family Firms Really More Socially Responsible?

Abstract: This paper conducts an empirical study as to whether family firms are more socially responsible than their nonfamily counterparts and explores the conditions in which this difference in social behavior occurs. We argue that family firms, given their socioemotional wealth bias, have a positive effect on social dimensions linked to external stakeholders, yet have a negative impact on internal social dimensions. Thus, family firms can be socially responsible and irresponsible at the same time. We also suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
491
5
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(575 citation statements)
references
References 79 publications
(99 reference statements)
26
491
5
6
Order By: Relevance
“…These expectations align with discussions in the family business literature about internal and external SEW (Cruz et al, 2014;Vardaman and Gondo, 2014). SEW may have both positive and negative influences in firm-level outcomes, including innovation, although the majority of scholars has considered the effects of SEW as primarily positive .…”
Section: Socioemotional Wealth Perspectivesupporting
confidence: 61%
See 2 more Smart Citations
“…These expectations align with discussions in the family business literature about internal and external SEW (Cruz et al, 2014;Vardaman and Gondo, 2014). SEW may have both positive and negative influences in firm-level outcomes, including innovation, although the majority of scholars has considered the effects of SEW as primarily positive .…”
Section: Socioemotional Wealth Perspectivesupporting
confidence: 61%
“…These non-monetary benefits are captured by the construct of SEW that Gomez-Mejia and colleagues have introduced first to the family business literature (Gomez-Mejia et al, 2007;Gomez-Mejia et al, 2010). Although scholars have so far emphasized the observed differences between family and non-family firms as separate grounds (Deephouse and Jaskiewitz, 2013;Cruz et al, 2014), differences within family businesses should also be considered, because family firms are also highly heterogeneous and different from one another. For instance, Miller et al (2007) report differences between family firms that are managed by founders and those managed by heirs.…”
Section: Socioemotional Wealth -Theoretical and Operational Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In essence, family members can rely on each other to make the best decision in the overall interest of the organisation, this can lead to people working well together (Kramer, Brewer & Hanna, 1996). Taking into account the CSR subject, one can refer to a profound international study by Cruz, Larraza-Kintana, Garce´s-Galdeano and Berrone (2014). Those authors concluded that in general FEs "can be socially responsible and irresponsible at the same time.…”
Section: The Universal Values For Family Enterprises In the Internatimentioning
confidence: 99%
“…It includes issues such as concern for corporate reputation, which could drive adoption of more environmentally sustainable practices [48] because the firm seeks a favorable organizational reputation [49]. Since families also pursue nonfinancial goals in order to guarantee transgenerational sustainability, they will invest in proactive environmental practices [45].…”
Section: Sew Theorymentioning
confidence: 99%